PROMOTING LETTERS TO INCREASE STUDENTS’ WRITING SKILL - Fitri Novia (Language and Education Journal, 2016)
Writing is one of important skills learned by students because everyone can express their ideas, opinion, feeling, and information on the paper. However, writing considers difficult for students. To overcome the students’ problem in writing, teachers can use various ways and authentic materials. One of them is by using letters. Therefore, the aim of this study was to find out whether or not students’ writing skill could increase by using letters. Quasi - experimental method was used which involved experimental and control groups. The samples consisted of 72 students of SMP Negeri 5 Kayuagung.Writing test was used to collect the data. Content validity and inter-rater reliability were used to measure the validity and reliability of instrument. To analyze the data, t-test was used. Based on the result, the value of t-obtained (5.495) was higher than value of t-table (1.9944) and pvalue (0.000) was lower than άvalue (0.05). It meant that the null hypothesis was rejected and the alternative hypothesis was accepted. In other words, letters could increase students’ writing skill.